Evaluation Effects of Quercetin on Liver Apoptosis in Streptozotocin-induced Diabetic Rat - AA Khaki (Journal of Medicinal Plants, 2009)
Background: Quercetin is a strong antioxidant and long-term treatment of STZ-diabetic animals and it has been shown to reduce oxidative stress.